2015
DOI: 10.1155/2015/706259
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Antioxidant Activity of Chitin and Chitosan Prepared from Pacific White Shrimp Waste

Abstract: Chitin and chitosan, valuable marine biopolymers, recovered from shrimp waste, are an abundant by-product of the shrimp processing industry in Vietnam, at an estimated 200000 metric tons per year. The obtained chitin and chitosan are characterized by their purity and functional properties. The polymers show good quality with low residual ash and protein content (<1%). The antioxidant potency of chitosan is evaluated by several different in vitro systems, including 1,1-diphenyl-2-picrylhydrazyl (DPPH) free r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 23 publications
(30 reference statements)
2
40
1
Order By: Relevance
“…The degree of deacetylation (DDA) of chitosan ranges from 50 to 100% depending on the source (Trung & Bao, 2015), preparation method (demineralization, deproteinization, and deacetylation conditions) (Cho, No, & Meyers, 1998;Hossain & Iqbal, 2014;Lertsutthiwong, How, Chandrkrachang, & Stevens, 2002;Sagheer et al, 2009), and the reversal of the process steps (Fernandez-Kim, 2004). The DDA of chitosan influences both its physicochemical properties (Cho et al, 1998;Hossain & Iqbal, 2014;Tolaimate et al, 2000) and its biological properties (Matsugo et al, 1998;Raafat & Sahl, 2009;Rajalakshmi, Krithiga, & Jayachitra, 2013;Trung & Bao, 2015;Wan, Xu, Sun, & Li, 2013). Naznin (2005) stated that the optimum conditions for chitosan production from shrimp shell in Bangladesh were observed at using 30% HCI for demineralization, 1.5 N NaOH for deproteinization, 50% NaOH for deacetylation and resulted in chitosan yield of 8.7%.…”
mentioning
confidence: 99%
“…The degree of deacetylation (DDA) of chitosan ranges from 50 to 100% depending on the source (Trung & Bao, 2015), preparation method (demineralization, deproteinization, and deacetylation conditions) (Cho, No, & Meyers, 1998;Hossain & Iqbal, 2014;Lertsutthiwong, How, Chandrkrachang, & Stevens, 2002;Sagheer et al, 2009), and the reversal of the process steps (Fernandez-Kim, 2004). The DDA of chitosan influences both its physicochemical properties (Cho et al, 1998;Hossain & Iqbal, 2014;Tolaimate et al, 2000) and its biological properties (Matsugo et al, 1998;Raafat & Sahl, 2009;Rajalakshmi, Krithiga, & Jayachitra, 2013;Trung & Bao, 2015;Wan, Xu, Sun, & Li, 2013). Naznin (2005) stated that the optimum conditions for chitosan production from shrimp shell in Bangladesh were observed at using 30% HCI for demineralization, 1.5 N NaOH for deproteinization, 50% NaOH for deacetylation and resulted in chitosan yield of 8.7%.…”
mentioning
confidence: 99%
“…• DPPH test, reducing power and lipid peroxidation inhibition activity) was also shown in the work of Trung and Bao (2015) for the chitosan with DD 87% and no molecular weight specification. Similar, higher-molecular forms of chitosan (HMW) did not show activity as a primary antioxidants in the work of Pasanphan et al (2010) and this lack of activity can be correlated with strong intra-and intermolecular hydrogen bonds resulting in the absence of hydrogen atoms that would be donated to break free radicals chain oxidation reactions.…”
Section: Antioxidative Activity Of Chitosanmentioning
confidence: 61%
“…Antioxidant properties of chitosan were also investigated. Trung and Bao studied the molecule extracted from L. vannamei [104]. Their study suggested that the antioxidant effect observed was based on the free radical scavenging activity and the reduction of potency.…”
Section: Chitin and Chitosanmentioning
confidence: 99%